Evolution analysis of FRIZZY PANICLE (FZP) orthologs explored the mutations in DNA coding sequences in the grass family (Poaceae) - Li,Jia; Zhang,Litian; G. Elbaiomy,Rania; Chen,Lilan; Wang,Zhenrong; Jiao,Jie; Zhu,Jiliang; Zhou,Wanhai; Chen,Bo; Soaud,Salma A.; Abbas,Manzar; Lin,Na; et al. (PeerJ, 2022)
FRIZZY PANICLE (FZP), an essential gene that controls spikelet differentiation and development in the grass family (Poaceae), prevents the formation of axillary bud meristems and is closely associated with crop yields. It is unclear whether the FZP gene or its orthologs were selected during the evolutionary process of grass species, which possess diverse spike morphologies. In the present study, we adopted bioinformatics methods for the evolutionary analysis of FZP orthologs in species of the grass family. Thirty-five orthologs with protein sequences identical to that of the FZP gene were identified from 29 grass species. Analysis of conserved domains revealed that the AP2/ERF domains were highly conserved with almost no amino acid mutations. However, species of the tribe Triticeae, genus Oryza, and C4 plants exhibited more significant amino acid mutations in the acidic C-terminus region. Results of the phylogenetic analysis showed that the 29 grass species could be classified into three groups, namely, Triticeae, Oryza, and C4 plants. Within the Triticeae group, the FZP genes originating from the same genome were classified into the same sub-group. When selection pressure analysis was performed, significant positive selection sites were detected in species of the Triticeae and Oryza groups. Our results show that the FZP gene was selected during the grass family’s evolutionary process, and functional divergence may have already occurred among the various species. Therefore, researchers investigating the FZP gene’s functions should take note of the possible presence of various roles in other grass species.
Keywords: Evolution analysis; FRIZZY PANICLE (FZP) orthologs gene; Poaceae; Selective pressure